Combined Genomic and Transcriptomic Screening of Candidate Genes for Asymmetric Oviduct Development in Hens - Ruijie Li; Xiang Song; Xiao Lin; Mingli Deng; Yin Liu; Tuoyu Geng; Daoqing Gong; Minmeng Zhao; Long Liu (Agriculture)
Background: While the mechanism of asymmetric gonadal development is generally understood, the mechanism of asymmetric oviduct development remains unclear. Methods: Right and left oviducts were collected from chick embryos at three developmental stages (Embryonic day 7.5, E9.5, and E11.5) for RNA-seq analysis (RNA-seq). Whole-genome resequencing (WGRS) was performed on hens with bilateral reproductive systems (a rare natural occurrence) and unilateral controls. These data were co-analyzed with public RNA-seq data of female embryonic gonads at different developmental stages (E4.5, E5.5, and E6.5) to screen for candidate genes affecting oviduct degeneration/development. Results: RNA-seq analyses showed that a total of 27, 10, and 38 DEGs were identified between the left and right oviducts at E7.5, E9.5, and E11.5, respectively. WGRS analyses revealed 1045 differentially mutated genes (DMGs) between bilateral (D) and unilateral (S) groups. Preliminary validation highlighted BMP7, PAK3, SLC6A11, PITX2, and SMC1B as candidate genes influencing oviduct asymmetry. Conclusions: This study provides insights into the genetic basis of asymmetric oviduct development and lays the groundwork for breeding hens with bilateral reproductive systems.